The Israeli-Palestinian Conflict - Halwani, R. author. aut Link
XVI, 285 p.
Keywords: This book addresses the ongoing conflict among Israeli Jews and Palestinian Arabs from a philosophical perspective. The authors argue that ignoring justice and failing to address violations of rights, including the rights of both Palestinians and Israelis to live securely and freely, then a lasting solution to the conflict will remain elusive.